Research on Interactive Control of Electrolytic Aluminum Load and Wind Power Output - Ge Simin; Yu Kun (MATEC Web of Conferences, 2016)
With the large-scale wind power generation connected to Gansu power grid, electrolytic aluminium load has reached a certain scale at the same time, the vast majority of electrolytic aluminium load directly connects to power grid using 330kV transmission line. According to the physical characteristics and historical data, the continuous adjustment characteristic of electrolytic aluminium load is analysed. Based on this characteristic, a mathematical model for the electrolytic aluminium load is established. Aiming at reducing power network loss and wind power consumption, an optimization model based on the load regulation characteristics of electrolytic aluminium is constructed, which is optimized by particle swarm optimization algorithm. Based on the case data of Gansu power grid, the optimal method based on the load regulation characteristics of electrolytic aluminium is analysed and its feasibility is verified.